KEY AREAS OF USE OF REMOTE SERVERS IN THE ACTIVITIES OF ECONOMIC ENTITIES (Uzbekistan Open Conference, 2025)
This article examines the use of remote servers in businesses and organizations.The authors examine the key functions and benefits of using remote servers, emphasizing the importance of effective remote server management.They also provide a comparative analysis of two main approaches to server management and review existing practices for implementing remote server management applications.The focus is on automating and simplifying the management process using specialized tools.Examples of successful implementation of such applications in various foreign and domestic organizations are provided, and the main challenges encountered when implementing remote server management applications are identified.The need for an integrated approach to project planning and implementation for the successful implementation and operation of these systems is emphasized.